[84] Management and outcome of peri-urethral lesions - Mustafa Hilmy (Taylor & Francis Group, 2018)
Objective: To present a series of cases of peri-urethral lesions that presented to the urology and gynaecology department over the last 5 years. Peri-urethral lesions are unusual presentation to uro-gynaecology clinics. Clinical diagnosis can be challenging due a broad differential including urethral diverticulum, caruncle, prolapse, peri-urethral cyst, vaginal wall cyst, and neoplasms of urethral or vaginal origin. Methods: A retrospective review of all patients who presented with peri-urethral lesions between November 2013 and June 2018. Data collected included presenting signs and symptoms, preoperative assessment, imaging, surgical management, and outcome. Results: In all, 26 patients were identified (age range 24–83 years). The most common presenting symptom was vaginal pain ± dyspareunia in 18/26 (69%). In eight of the 26 (31%) the main symptom was a vaginal lump, seven (27%) had recurrent urinary tract infections, four (15%) had stress urinary incontinence, three (12%) had voiding dysfunction, and one (4%) was asymptomatic. On clinical examination, all patients were found to have a solitary vaginal lump measuring 1–4 cm. Five (19%) patients were treated conservatively. In all, 21 (81%) had trans-vaginal complete excision. Histological examination confirmed the diagnosis of urethral diverticulum in 15 patients (58%), Skene’s duct cysts in three, and Müllerian cyst and arterio-venous malformation one of each. There were no significant postoperative complications. Magnetic resonance imaging (MRI) findings did not match the histological diagnosis in nine of the 26 (35%) patients. The median follow-up period was 6 months and 10/21 (48%) had complete resolution of their symptoms. Five of 21 (24%) patients had persistent pain and have been treated conservatively by the pelvic floor physiotherapist or pain team, three of 21 (14%) had recurrent urinary symptoms and repeated MRI in two of them was negative. Three patients are still awaiting follow-up. Conclusion: Peri-urethral lesions are uncommon but can be a challenging. MRI can be useful in diagnosis and to plan intervention, but in up to one-third the findings did not match the histological diagnosis. Surgical excision will alleviate symptoms with a small risk of recurrence of symptoms.